2017
DOI: 10.1002/cncr.30845
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of recombinant human lymphotoxin‐α derivative with cisplatin and fluorouracil in patients with metastatic esophageal squamous cell carcinoma: A randomized, multicenter, open‐label, controlled, phase 2b trial

Abstract: rhLTα-Da combined with the PF regimen failed to improve PFS and ORR in patients with mESCC, except in a small subset that had low serum TNFR II concentrations. Cancer 2017;123:3986-94. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…The median OS and median PFS were 8.5 and 4.0 months in the CT-CONT arm, respectively, and 8.8 and 1.4 months in the CT-DISC arm, respectively. Although one could have anticipated a better OS for patients in the CT-CONT arm that, actually, had been selected on the basis of early control of their disease, our survival results are of the same order of magnitude to those previously reported with FU/platinum regimens in contemporary randomised-studies [17][18][19]. E-DIS was not designed to detect a superiority of one arm over the other.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The median OS and median PFS were 8.5 and 4.0 months in the CT-CONT arm, respectively, and 8.8 and 1.4 months in the CT-DISC arm, respectively. Although one could have anticipated a better OS for patients in the CT-CONT arm that, actually, had been selected on the basis of early control of their disease, our survival results are of the same order of magnitude to those previously reported with FU/platinum regimens in contemporary randomised-studies [17][18][19]. E-DIS was not designed to detect a superiority of one arm over the other.…”
Section: Discussionsupporting
confidence: 51%
“…The role of chemotherapy has not yet been fully established in the treatment of metastatic ESCC (mESCC) [4]. Many cytotoxic drugs promote tumor shrinkage [5][6][7][8][9][10][11][12][13][14][15][16][17] but, until now, there has been no randomised trial that provides unequivocal evidence for a clinical benefit with chemotherapy. For example, the European Organisation for Research and Treatment of Cancer (EORTC) reported the results of a randomised phase 2 trial that compared the activity of cisplatin (CDDP) with or without 5-fluorouracil (FU) in 88 mESCC [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, upon systemic use of the LTα derivative rhLTα‐Da, the patient showed significant systemic response due to the proinflammatory effect, presenting with fever, chills, hypertension, etc. [ 43 ]. Therefore, we focussed on tumour cells, attempting to explore the feasibility of achieving therapeutic effects by local overexpression of LTα.…”
Section: Discussionmentioning
confidence: 99%
“…As ESCC is the major histologic form of esophageal cancer in East Asian countries, the same regimen was repeated with lower doses of both drugs in China and Japan [10,11,18]. Compared with the Western studies, while the dose reduction did not reduce the efficacy (table 4), toxicity was comparable and chemotherapy-related deaths still occurred [8,9,10,11,17,18]. This finding further underscores the need for identifying new treatment approaches in this disease.…”
Section: Discussionmentioning
confidence: 99%